Las grandes mascotas - Smith, Lane.; Loyo, Ernestina (Mexico, D.F. : Fondo de Cultura Econonica, 1993)
A little girl explores the mysterious dreamworld where small children play with their big pets, which range from cats and dogs to snakes and crickets.
Translation of: The big pets.
Accelerated Reader AR
Keywords: Pets -- Fiction; Dreams -- Fiction; Animales -- Novela juvenil; Animales caseros -- Novela juvenil; Suenos -- Novela juvenil; Spanish language materials -- Fiction; Fiction